Simulating age-related changes in carbon storage and allocation in a Chinese fir plantation growing in southern China using the 3-PG model - Zhao, Meifang; Xiang, Wenhua; Peng, Changhui; Tian, Dalun (Forest Ecology and Management, 2009)

Marginal effects of silvicultural treatments on soil nutrients following harvest in a Chinese fir plantation - Xiang, Wenhua; Chai, Hongxia; Tian, Dalun; Peng, Changhui (Soil Science and Plant Nutrition, 2009)

Meta-analysis and its application in global change research - Lei, XiangDong; Peng, ChangHui; Tian, DaLun; Sun, JianFeng (Chinese Science Bulletin, 2007)

Land use change in Asia and the ecological consequences - Zhao, Shuqing; Peng, Changhui; Jiang, Hong; Tian, Dalun; Lei, Xiangdong; Zhou, Xiaolu (Ecological Research, 2006)
Abstract Viewed within a historical context, Asia has experienced dramatic land transformations, and currently more than 50% of Asian land area is under agriculture. The consequences of this transformation are manifold. Southeast Asia has the highest deforestation rate of any major tropical region. Many of the world's large rivers and lakes in Asia have been heavily degraded. About 11 of 19 world megacities with more than 10 million inhabitants are in Asia. These land use activities have resulted in substantial negative ecological consequences, including increased anthropogenic CO 2 emissions, deteriorated air and water quality, alteration of regional climate, an increase of disease and a loss of biodiversity. Although land use occurs at the local level, it has the potential to cause ecological impact across local, regional and global scales. Reducing the negative environmental impacts of land use change while maintaining economic viability and social acceptability is an major challenge for most developing countries in Asia.

Variation in runoff with age of Chinese fir plantations in Central South China - Tian, Dalun; Yan, Wende; Chen, Xiaoyong; Deng, Xiangwen; Peng, Yuanying; Kang, Wenxing; Peng, Changhui (Hydrological Processes, 2008)
Abstract To determine the influence of forest structures on runoff characteristics, the hydrological effects of Chinese fir plantations were studied by analysing runoff patterns at different growth and development stages (stand age classes I to V) from 1984 to 2004 at the Huitong Ecosystem Research Station, Central South University of Forestry and Technology, Hunan Province, Central South China. Results for two small experimental Chinese fir watersheds showed different peak values for surface runoff amount and coefficients at different ages, with lowest values in age classes I and V and highest values in age classes II and III. However, both underground and total runoff coefficients decreased with increasing age class. Total runoff coefficient was about twice as high in age class I (30·8%) as that in age class V (15·8%). Higher underground and total runoff coefficients were found in young forests. This was mainly attributed to soil disturbance due to human management practices such as site ploughing. Results indicate that Chinese fir plantations play a significant role in regulating water distribution in the watershed. Useful information is provided on the effects of forest management practices on hydrological processes in forest plantations. Copyright © 2008 John Wiley & Sons, Ltd.

Heavy metal accumulation by panicled goldenrain tree (Koelreuteria paniculata) and common elaeocarpus (Elaeocarpus decipens) in abandoned mine soils in southern China - Tian, Dalun; Zhu, Fan; Yan, Wende; Xi, Fang; Xiang, Wenhua; Deng, Xiangwen; Wang, Guangjun; Peng, Changhui (Journal of Environmental Sciences, 2009)